Association Between HTLV-1 Infection and Nasopharyngeal Carcinoma: A Case-Control Study - Hosseini, Sare; Kalantari, Mahmoudreza; Kalantari, Shakiba; Majidi, Mohammad Reza; Rafatpanah Baygi, Houshang; Javadinia, Seyed Alireza (Reports of Radiotherapy and Oncology, 2023)
Background: The northeast of Iran is one of the endemic regions of human T-cell lymphotropic virus type-1 (HTLV-1). This study aimed to evaluate the relationship between nasopharyngeal carcinoma and HTLV-1 infection in northeast Iran, an endemic area for HTLV-1. Methods: In this case-control study, paraffin-embedded nasopharyngeal tissue samples of patients with definitive nasopharyngeal carcinoma were evaluated for the presence of the HTLV-1 genome by polymerase chain reaction retrospectively. Results: Thirty patients with nasopharyngeal carcinoma and 30 healthy people were evaluated. All participants were matched in terms of age and gender, and all were living in Mashhad. The HTLV-1 genome was detected in only one of the people in the healthy group. Conclusions: The HTLV-1 infection and nasopharyngeal carcinoma did not correlate significantly.